2021
DOI: 10.3390/v13091817
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antiviral Properties of Industrially Important Marine Algal Polysaccharides and Their Significance in Fighting a Future Viral Pandemic

Abstract: Over the decades, the world has witnessed diverse virus associated pandemics. The significant inhibitory effects of marine sulfated polysaccharides against SARS-CoV-2 shows its therapeutic potential in future biomedical applications and drug development. Algal polysaccharides exhibited significant role in antimicrobial, antitumor, antioxidative, antiviral, anticoagulant, antihepatotoxic and immunomodulating activities. Owing to their health benefits, the sulfated polysaccharides from marine algae are a great d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 165 publications
1
14
0
1
Order By: Relevance
“…More than 53% of the global agar production is derived from two primary species of red seaweed, namely Gracilariopsis and Gracilaria, as highlighted by Nasrollahzadeh et al [98]. The high antiviral activity of agarans, evaluated mainly against herpes simplex virus HSV-1 and HSV-2 from the encapsulated viruses [99][100][101][102], is considered to be correlated with the high-molecular-weight galactan sulfate fractions [103] and is mediated through direct interaction with the virus particle rather than by interaction with the host cells or with erythrocytes [104]. Currently, there is only one study, that of Farfour et al, 2022, that has investigated the dynamics of SARS-CoV-2 directly in agar media.…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…More than 53% of the global agar production is derived from two primary species of red seaweed, namely Gracilariopsis and Gracilaria, as highlighted by Nasrollahzadeh et al [98]. The high antiviral activity of agarans, evaluated mainly against herpes simplex virus HSV-1 and HSV-2 from the encapsulated viruses [99][100][101][102], is considered to be correlated with the high-molecular-weight galactan sulfate fractions [103] and is mediated through direct interaction with the virus particle rather than by interaction with the host cells or with erythrocytes [104]. Currently, there is only one study, that of Farfour et al, 2022, that has investigated the dynamics of SARS-CoV-2 directly in agar media.…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%
“…In addition, seaweed polysaccharides can inhibit viral transcription and replication through direct interference with viral replication enzymes or inhibition on other intracellular targets [ 140 ]. Marine polysaccharides, especially sulfated polysaccharides from marine algae, appear to block viral infection by inhibition of one or more of these stages, with the specific mechanisms dependent on the structure of the individual polysaccharide [ 140 , 141 , 142 , 143 , 144 ].…”
Section: Conclusion and Future Outlooksmentioning
confidence: 99%
“…Starting with the first reported antiviral polysaccharides against mumps and influenza [ 1 , 2 ], several other reports have suggested that polysaccharides and their derivatives are potent antivirals [ 3 ]. The inhibition of human immunodeficiency virus 1 (HIV-1) by polysaccharides and their derivatives was also one of the reported antiviral activities [ 4 , 5 , 6 ]. Studies have also shown that sulfated polysaccharides from different sources showed beneficial effects against HIV infection either inhibiting cell entry or viral replication [ 7 ].…”
Section: Introductionmentioning
confidence: 99%